2023
DOI: 10.1128/spectrum.01481-23
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of TelE, a T7SS LXG Effector Exhibiting a Conserved C-Terminal Glycine Zipper Motif Required for Toxicity

Abstract: In this study, 38 clinical isolates of Streptococcus gallolyticus subsp. gallolyticus ( SGG ) were sequenced and a genetic locus encoding the type VIIb secretion system (T7SSb) was found conserved and absent from 16 genomes of the closely related S. gallolyticus subsp. pasteurianus ( SGP ). The T7SSb is a bona fide pathogenicity island.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…We next wanted to test if the protein product of each gene required for TelA secretion is exported from cells. We and others previously found that the targeting factors for TelC toxins, LapC1 and LapC2, are not secreted from cells (12,15). To test if this is also the case for LapA3 and LapA4, we expressed C-terminal VSV-G tagged versions of these proteins and performed western blot analyses on cell and culture supernatant fractions of wild-type and T7SS-null (DessC) strains of Si B196 .…”
Section: Identification Of Two New Families Of Lxg Toxin Targeting Fa...mentioning
confidence: 98%
“…We next wanted to test if the protein product of each gene required for TelA secretion is exported from cells. We and others previously found that the targeting factors for TelC toxins, LapC1 and LapC2, are not secreted from cells (12,15). To test if this is also the case for LapA3 and LapA4, we expressed C-terminal VSV-G tagged versions of these proteins and performed western blot analyses on cell and culture supernatant fractions of wild-type and T7SS-null (DessC) strains of Si B196 .…”
Section: Identification Of Two New Families Of Lxg Toxin Targeting Fa...mentioning
confidence: 98%
“…that encodes a putative type VII secretion system contributing to gut colonization and the development of colon tumors [ 19 ]. Teh et al in 2023 further characterized one of the type VII secretion system effector proteins, named herein TelE, exhibiting their toxic activity of promoting the loss of membrane integrity [ 20 ]. Pasquereau-Kotula et al demonstrate the oncogenic role of Sgg.…”
Section: Discussionmentioning
confidence: 99%
“…A further TelE LXG toxin has also been described in Streptococcus gallolyticus [ 17 ]. TelE carries a bacteriocin-like glycine zipper motif, which inserts into and destabilises target membranes, and is homologous to S. aureus EsxX.…”
Section: The T7ssb As a Bacterial Weaponmentioning
confidence: 99%
“… S. aureus EsxC, EsxB and EsxD have previously been shown to be secreted substrates, suggesting they are co-secreted with EsaD. Similarly, two small WXG100-like proteins encoded directly upstream of the S. gallolyticus LXG toxin TelE are T7-secreted [ 17 ]. The streptococcal Lap proteins are secreted with their cognate LXG domain protein in some cases but not all [ 72, 82 ], although it remains a possibility that these proteins are degraded following secretion and so not detected in the secretome.…”
Section: Strain-specific Secretion Factors and T7ss Targeting Signalsmentioning
confidence: 99%
See 1 more Smart Citation